2019
DOI: 10.1080/1343943x.2018.1561196
|View full text |Cite
|
Sign up to set email alerts
|

Combine harvesting efficiency as affected by rice field size and other factors and its implication for adoption of combine contracting service

Abstract: Small combine harvesters have become popular in SE Asia recently, but small rice fields appear to limit its field operation and hence its wide adoption by smallholders. Combine harvesting efficiency, the area of paddy field harvested per unit time, was determined for 6 seasons in Central Lao PDR for over 400 fields varying in size and toposequence position, rice varieties grown, crop establishment methods and crop conditions particularly lodging at harvest. Combine harvesting efficiency was commonly about 3 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Combine harvested crops do not require the additional threshing process as it is in-built in the combine harvester, and this again saves further time and cost. Economic analysis indicates large benefits to farmers adopting combine harvesting contracting service, particularly in areas with high labour cost (Bunna et al, 2018;Xangsayasane et al, 2019c). Their study also indicated that combine harvested grain yield was similar to hand harvested yield and grain harvesting loss was about 1.5% of the total yield, which was less than the total loss for manual harvested crops when the losses during threshing and handling of paddies was included.…”
Section: Combine Harvestermentioning
confidence: 95%
See 4 more Smart Citations
“…Combine harvested crops do not require the additional threshing process as it is in-built in the combine harvester, and this again saves further time and cost. Economic analysis indicates large benefits to farmers adopting combine harvesting contracting service, particularly in areas with high labour cost (Bunna et al, 2018;Xangsayasane et al, 2019c). Their study also indicated that combine harvested grain yield was similar to hand harvested yield and grain harvesting loss was about 1.5% of the total yield, which was less than the total loss for manual harvested crops when the losses during threshing and handling of paddies was included.…”
Section: Combine Harvestermentioning
confidence: 95%
“…In the province, 24 combines (Kubota DC70) are now available compared to 2 in 2015 (Table 1), and they are mostly operated by contractors. When the fees are based on 10-20% of the crop produced with a yield of 2.3-3.2t/ ha (Table 4), the charge is in the range of 69-190USD/ha (Xangsayasane et al, 2019c). While combine service fees have become cheaper in Laos including Khammouan from (Bunna et al, 2018).…”
Section: Combine Harvestermentioning
confidence: 99%
See 3 more Smart Citations